THE EFFECT OF TAX UNDERSTANDING, TAX RATES, TAX INCENTIVES AND TAX SANCTIONS ON TAX PAYERS COMPLIANCE OF MSME IN NGAWI DURING THE COVID-19 PANDEMIC - Diah Mutiara Nurhayati; Banu Witono (Jurnal Ilmiah Akuntansi & Bisnis, 2022)
This study aims to examine the effect of tax understanding, tax rates,tax incentives, and tax sanction to the tax payers compliance of Micro Small and Medium Enterprises (MSMEs) in Ngawi, Indonesia during the Covid-19 pandemic. This study uses primary data where data collection uses a questionnaire . Data collection method is by distributing questionnaires to tax payers of Micro Small and Medium Enterprises (MSMEs) in Ngawi, Indonesia. The sample used is 84 respondent. In this study using quantitative data analysis methods by classic test consisting of the normality test, the multicollonearity assumtion test, the heteroskedastisitas test, multiple linear regression analysis, hypothesis testing, and the coefficient of determination (R2) test. The research results showed that the variables tax understanding, tax incentives, and tax sanction has an effect while tax rates hasn’t effect for MSME tax payers compliance.